2017
DOI: 10.5658/wood.2017.45.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Driving Rain Index in Korea

Abstract: This research was performed to evaluate the level of exposure of buildings to rain in Korea. The impingement of driving rain by wind is evaluated by driving rain index (DRI). Average annual driving rain indexes (AADRI) for 64 stations spread all over Korea have been determined by using the data of wind speed and precipitation obtained from Korea Meteorological Adminstration (KMA). Based on the values, the regions has been classified as low, moderate, and high. No high exposure regions were found in Korea; 22 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In previous research performed by Ra (2017), the DRI was determined by using daily climate data. Some studies have used daily data instead of hourly data to calculate driving rain index because it is difficult to obtain the climate data for the consecutive periods of 30 years that is known as climatological normals (Chand and Bhargava, 2002).…”
Section: Domestic Hourly Climatic Data From 2009 To 2017mentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research performed by Ra (2017), the DRI was determined by using daily climate data. Some studies have used daily data instead of hourly data to calculate driving rain index because it is difficult to obtain the climate data for the consecutive periods of 30 years that is known as climatological normals (Chand and Bhargava, 2002).…”
Section: Domestic Hourly Climatic Data From 2009 To 2017mentioning
confidence: 99%
“…In Korea Ra (2017) investigated DRI for 82 locations spread all over the country by using daily-based climate data and reported that there were no high exposure regions. However, there was a need for additional research because the hourly-based climate data can gives a better estimation than the daily-based data.…”
Section: Introductionmentioning
confidence: 99%
“…Based on its results, it is possible to build an optimal and logically justified chain of all logging operations (Sushkov et al, 2015). Despite the relevance and importance of these studies, an obvious drawback should be noted -their use is limited by the static environment (Ra, 2017;. At the same time, the forest area is a dynamically changing environment.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the forest area is a dynamically changing environment. The constantly changing environmental conditions also influence the efficiency of the logging process (Kim and Ra, 2014;Ra, 2017;. Thus, there is a need to develop theoretical research precisely taking into account the dynamics of environmental change.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several climate indexes based on temperature-rainfall combinations have been developed to help designers and builders (Lstiburek, 2001;Russo, 1971). They were determined based on either wind-driven rain or the decay risk of wood used for exterior aboveground applications (Boyd, 1963;Kim et al, 2011;Ra, 2013, 2014;Ra, 2017;Setliff, 1986). Although these climate classifications were useful, they were not developed to evaluate potential moisture loading on the envelopes of materials, such as wood.…”
Section: Introductionmentioning
confidence: 99%